Microsatellite markers for Russian olive (Elaeagnus angustifolia; Elaeagnaceae)1. (2nd September 2013) - Gaskin, John F.; Hufbauer, Ruth A.; Bogdanowicz, Steven M.
Abstract : Premise of the study: Microsatellite markers were developed for the plant species Elaeagnus angustifolia to assist in future investigations of genetic variability in its native and invasive ranges and the precise origins of the United States/Canada invasion. Methods and Results: Eleven polymorphic microsatellite markers were developed. The number of alleles observed for each locus ranged from three to 11. Conclusions: These microsatellites have sufficient potential variability to define population structure and origins of the Russian olive invasion.